MORPHOLOGICAL PATTERN AND FREQUENCY OF CENTRAL NERVOUS SYSTEM TUMOURS IN CHILDREN - Fatima, Bilqees; Khaleeq, Samina; Tahir, Mohammad; Zaman, Khaleeq uz (Journal of Ayub Medical College Abbottabad, 2016)
Background: Recent studies, including a comprehensive study by National Cancer Institute, have shown that a significant increase in the incidence of childhood brain tumours makes them the most common paediatric tumour. The objectives of this study were to determine the frequency of central nervous system tumours in paediatric age group (0-12 years), and to segregate various morphologic types according to WHO classification. Methods: The study included consecutive cases of central nervous system tumours diagnosed in children in the histopathology department at Federal Government Polyclinic, PGMI, Islamabad, during a period of 4.8 years (Jan 2009-Aug 2013). The initial histopathological evaluation of these lesions was performed on H&E stained sections of paraffin embedded tissues. Special stains and immunohistochemistry were performed whenever indicated. Results: Out of 75 cases, 34 (45.3%) were astrocytic tumours, including 16(47.1%) Pilocytic astrocytomas (WHO Grade-I), 1 (2.9%) diffuse fibrillary astrocytoma (WHO Grade-II), 1 (2.9%) anaplastic astrocytoma (WHO Grade-III) and 16(47.1%) glioblastoma multiforme (WHO Grade-IV); 18 (24%) were embryonal tumours including 17 (94.4%) medulloblastoma (WHO Grade-IV) and 1 (5.6%) neuroblastoma (WHO Grade IV); 10 (13.3%) were craniopharyngiomas (WHO Grade-I) and 5 (6.7%) were ependymal tumours including 1 (20%) myxopapillary ependymoma (WHO Grade-I) and 4 (80%) ependymomas (WHO Grade-II). Miscellaneous entities included 3 (4%) choroid plexus tumours; 1 (2%) anaplastic oligodendroglioma (WHO Grade-III); 1 (2%) atypical meningioma (WHO Grade-II); 1 (2%) schwannoma (WHO Grade-I); 1 (2%) neurofibroma (WHO Grade-I) and 1 (2%) lipoma (WHO Grade-I). Conclusion: Astrocytic tumours are the most common central nervous system tumours in paediatric age group and high grade lesions (WHO Grade-IV) constitute the largest category (45.3%).